Maritime supply chain sustainability: South-East Finland case study - Oskari Lähdeaho; Olli-Pekka Hilmola; Riitta Kajatkari (Journal of Shipping and Trade, 2020)
Abstract Emphasis on sustainability practices is growing globally in the shipping industry due to regulations on emissions from transportation as well as increasing customer demand for sustainability. This research aims to shed light on the environmental sustainability of companies involved in maritime logistics at the major Finnish seaport, HaminaKotka. This seaport is a part of International Maritime Organization’s (IMO) Baltic and North Sea emission control area, with special emission-reducing measures contributing directly to United Nations’ Sustainable Development Goals (SDGs) by mitigating negative impacts of industrial activity on environment and climate change. Two semi-structured interviews with companies at HaminaKotka were carried out to construct a case study examining the sustainability challenges at hand. In addition, experience of one of the authors in a managerial position at the studied seaport complex, as well as the sustainability communications of the companies situated in the area were used to support the findings. The companies improve environmental sustainability by using multimodal transport chains, alternative fuels in the transports, and environmental sustainability demands towards their partners. However, the most important measures, according to these companies, are transport mode selection and cargo load optimization. Moreover, companies have identified bottlenecks of cargo flow at the hinterland due to road infrastructure constraints. As regulations and customers are requiring environmental sustainability, companies are forced to renew their operations, strategy and business models. Especially, the emission-reducing regulations drive companies to implement means to control the produced emissions.